Involvement of Potassium Channels in Vasorelaxant Effect Induced by Valeriana prionophylla Standl. in Rat Mesenteric Artery - Reis, Milena Ramos (Hindawi Publishing Corporation, 2013)
Assays in vitro and in vivo were performed on extract from roots and leaves from the Valeriana prionophylla Standl. (VPR and VPF, resp.). In phenylephrine (1 μM) precontracted rings, VPR (0.01–300 μg/mL) induced a concentration-dependent relaxation (maximum response (MR) = 75.4 ± 4.0%, EC(50) = 5.97 (3.8–9.3) μg/mL, n = 6]); this effect was significantly modified after removal of the endothelium (EC(50) = 39.6 (27.2–57.6) μg/mL, P < 0.05). However, VPF-induced vasorelaxation was less effective compared to VPR. When rings were preincubated with L-NAME (100 μM) or indomethacin (10 μM), the endothelium-dependent relaxation induced by VPR was significantly attenuated (MR = 20.9 ± 2.3%, 34.2 ± 2.9%, resp., P < 0.001). In rings denuded endothelium, precontracted with KCl (80 mM), or in preparations pretreated with KCl (20 mM) or tetraethylammonium (1 or 3 mM), the vasorelaxant activity of VPR was significantly attenuated (MR = 40.0 ± 8.2, n = 5; 50.5 ± 6.0%; 49.3 ± 6.4%; 46.8 ± 6.2%; resp., P < 0.01). In contrast, neither glibenclamide (10 μM), barium chloride (30 μM), nor 4-aminopyridine (1 mM) affected VPR-induced relaxation. Taken together, these results demonstrate that hypotension induced by VPR seems to involve, at least in part, a vascular component. Furthermore, endothelium-independent relaxation induced by VPR involves K(+) channels activation, most likely due to BK(Ca) channels, in the rat superior mesenteric artery.